Investigating the Effect of an Acceptance and Commitment Therapy-Based Psychoeducation Programme on Levels of Psychological Flexibility, Death Anxiety, Burnout and Life Satisfaction in Parents of Disabled Children - Marufoğlu, Mevlüt; Tanhan, Fuat (Border Crossing, 2025)
This study examined the effect of an Acceptance and Commitment Therapy (ACT)-based psychoeducation program on levels of psychological flexibility, death anxiety, burnout, and life satisfaction in parents of disabled children. The study used a 3 X 3 split-plot mixed experimental design including experimental, control, and placebo groups, and a pretest, posttest, and follow-up test were administered to each group. The study group comprised parents of disabled children attending special education and rehabilitation centers in the Ercis district of Van province. The study data were collected using a sociodemographic information form, the Acceptance and Action Questionnaire-II (AAQ-II), the Thorson-Powell Death Anxiety Scale, the Maslach Burnout Inventory, and the Satisfaction with Life Scale. As a result, it was observed that the applied psychoeducation program increased psychological flexibility and life satisfaction levels in parents of disabled children at a statistically significant level. In contrast, the changes in their death anxiety and burnout levels were not statistically significant.